2018
DOI: 10.1155/2018/4894705
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Method for Detecting Ara h 2 by Generation and Utilization of Monoclonal Antibodies

Abstract: Peanut (Arachis hypogaea) is one of the most common food allergens that can induce fatal anaphylaxis, and Ara h 2 is one of the major allergen components involved in peanut allergy. The aim of this study was to develop a quantitative method for detecting peanut allergen using monoclonal antibodies against Ara h 2. The splenocytes of immunized mice were fused with myeloma cells (SP2/0), and stable mAb-producing clones were obtained by limiting dilution. mAbs against Ara h 2 were isolated from mouse ascites, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…We also compared the sensitivities and target antigens of the developed indirect ELISA to immunoassays reported in other reports [ 36 - 38 ] ( Table 2 ). The lateral flow immunoassay is specific to native purified Ara h 1, and sandwich ELISA based on a monoclonal antibody specific to recombinant Ara h 2 of peanuts has been reported previously.…”
Section: Resultsmentioning
confidence: 99%
“…We also compared the sensitivities and target antigens of the developed indirect ELISA to immunoassays reported in other reports [ 36 - 38 ] ( Table 2 ). The lateral flow immunoassay is specific to native purified Ara h 1, and sandwich ELISA based on a monoclonal antibody specific to recombinant Ara h 2 of peanuts has been reported previously.…”
Section: Resultsmentioning
confidence: 99%
“…In ELISA, allergens can be detected by the colorimetric reaction after binding of the antigen with the specific enzyme-labeled antibody. Earlier studies reported the allergenic proteins quantification in peanut-based products through ELISA and HPLC technique (29, 3335), however, no information on peanut seeds. The key issues in ELISA are the sample preparation and unacceptable variability in multiple measurements of the same sample.…”
Section: Introductionmentioning
confidence: 99%